NEDD4 controls intestinal stem cell homeostasis by regulating the Hippo signalling pathway. - Bae, S.J.; Kim, M.; Kim, S.H.; Kwon, Y.E.; Lee, J.H.; Kim, J.; Chung, C.H.; Lee, W.J.; Seol, J.H. (Nature communications, 2015)
The Hippo pathway plays crucial roles in regulating organ size and stem cell homeostasis. Although the signalling cascade of the core Hippo kinases is relatively well understood, little is known about the mechanisms that modulate the activity of the Hippo pathway. Here, we report identification of NEDD4, a HECT-type E3 ubiquitin ligase, as a regulatory component of the Hippo pathway. We demonstrate that NEDD4 ubiquitylates and destabilizes WW45 and LATS kinase, both of which are required for active Hippo signalling. Interestingly, MST1 protects WW45, but not LATS2, against NEDD4. We also provide evidence indicating that NEDD4 inactivation at high cell density is a prerequisite for the elevated Hippo activity linked to contact inhibition. Moreover, NEDD4 promotes intestinal stem cell renewal in Drosophila by suppressing Hippo signalling. Collectively, we present a regulatory mechanism by which NEDD4 controls the Hippo pathway leading to coordinated cell proliferation and apoptosis.